Music Education, Creativity and Technology: An Exploratory Study on Teaching Strategies and Creative Activities With Ex Novo Software - Riaño, Maria Elena; Murillo, Adolf; Tejada, Jesús (Revista Electrónica Educare, 2022)
Objective. To analyze the strategies and creative activities that music teachers carry out in their classrooms using software created by researchers that facilitates collaborative sound creation in educational contexts. Method. The work was carried out using an exploratory-descriptive approach through a didactic experience developed during 12 weeks in the classroom; after, 27 primary and secondary education teachers were surveyed. The survey collected information on classroom activities, creative processes conducted, teaching strategies adopted by teachers, classroom resources, and the use of software in the activities. Results. The findings show: 1) a managerial style of the teaching staff; 2) creative activities that were mostly limited to the soundization of images and stories; 3) a middle-lower hourly dedication in the classroom; 4) positive perceptions about cooperative work and the creativity of the students; 5) a positive evaluation of the software; 6) a large number of problems in understanding the software. Conclusions. It is suggested that there is a need for greater involvement of teachers in creative composition processes, as well as for more and better technological training of teachers.